Mediation in Traditional Medicine Conflicts in Indonesia - Pertiwi, Yuniariana; Kintoko; Suliyanto; Nuryanto, Edy; Nuryanto, Abid (International Journal of Science and Society, 2025)
Conflict is considered an inevitable aspect and occurrence in human social relationships across all organizations. Conflict is a situation where differences in opinions, goals, or interests arise between two or more parties, potentially leading to tension, disputes, or disagreements. Conflicts can occur in various contexts, such as within families, organizations, societies, or even at the international level, and require proper resolution to prevent escalation into larger problems. Conflict can be understood as a disagreement arising between what someone expects from themselves, others, organizations, and what they experience in reality. If left unresolved, conflict can negatively impact a company or organization. However, conflict can also have positive impacts, such as increasing motivation, reducing stress, alerting leaders to unresolved issues, and encouraging both parties to engage in self-reflection. Addressing conflict effectively can ensure similar events do not recur and foster mutual respect among conflicting parties, leading to improved collaboration and productivity. This analysis focuses on describing mediation in traditional medicine conflicts in Indonesia using bibliometric literature analysis from 1973 to 2023 and examining scientific trends. The researchers used Scopus as a search engine, utilizing the keywords: Conflict OR Conflict Factors AND Traditional Medicine. Articles were selected from journals written in English and Indonesian. A total of 980 documents were retrieved for the period of 1979-2023. Vosviewer analysis revealed that research related to conflict and mediation in the pharmaceutical field is still lacking, highlighting the importance of conducting studies on mediation in conflict management within the traditional medicine sector. Although the number of publications has steadily increased, it remains below 40 per year. Interventions in topics such as experimental studies or compliance remain limited. Several countries experiencing increased conflicts have shown significant growth in the number of publications and collaborative studies over the past decade. The modest number of studies indicates that researchers still have numerous opportunities to develop better and more productive techniques to reduce and manage conflicts effectively.